Biased Signaling Favoring G(i) over β-Arrestin Promoted by an Apelin Fragment Lacking the C-terminal Phenylalanine - Ceraudo, Emilie (American Society for Biochemistry and Molecular Biology, 2014)
Apelin plays a prominent role in body fluid and cardiovascular homeostasis. We previously showed that the C-terminal Phe of apelin 17 (K17F) is crucial for triggering apelin receptor internalization and decreasing blood pressure (BP) but is not required for apelin binding or G(i) protein coupling. Based on these findings, we hypothesized that the important role of the C-terminal Phe in BP decrease may be as a G(i)-independent but β-arrestin-dependent signaling pathway that could involve MAPKs. For this purpose, we have used apelin fragments K17F and K16P (K17F with the C-terminal Phe deleted), which exhibit opposite profiles on apelin receptor internalization and BP. Using BRET-based biosensors, we showed that whereas K17F activates G(i) and promotes β-arrestin recruitment to the receptor, K16P had a much reduced ability to promote β-arrestin recruitment while maintaining its G(i) activating property, revealing the biased agonist character of K16P. We further show that both β-arrestin recruitment and apelin receptor internalization contribute to the K17F-stimulated ERK1/2 activity, whereas the K16P-promoted ERK1/2 activity is entirely G(i)-dependent. In addition to providing new insights on the structural basis underlying the functional selectivity of apelin peptides, our study indicates that the β-arrestin-dependent ERK1/2 activation and not the G(i)-dependent signaling may participate in K17F-induced BP decrease.